1991
DOI: 10.1063/1.348829
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of high-power microwave reflection, transmission, and absorption from a plasma-covered plane conducting boundary

Abstract: Experimental studies of the reflection, transmission, and absorption of high-power microwave pulses from a plasma-covered plane conducting boundary are presented. Under optimum conditions, backscattered rf power is attenuated by more than 30 dB over values measured in the absence of the plasma. Measurements of the radial and axial plasma density profiles and the neutral gas pressure near the plane conductor indicate that collisional absorption processes are not the primary source of the observed attenuation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…Thinking of the problem in an inverse manner, plasma parameters can be controlled to obtain a desired distribution of the scattered power. The latest approach has many applications in the design of the plasma-coated scatterers, [2,3] in which enhancing or reducing the scattered power in certain directions can be achieved via control of the plasma parameters and dimensions. However, several theoretical studies have been reported on the electromagnetic waves scattering from plasma with different shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Thinking of the problem in an inverse manner, plasma parameters can be controlled to obtain a desired distribution of the scattered power. The latest approach has many applications in the design of the plasma-coated scatterers, [2,3] in which enhancing or reducing the scattered power in certain directions can be achieved via control of the plasma parameters and dimensions. However, several theoretical studies have been reported on the electromagnetic waves scattering from plasma with different shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature plasma at atmospheric pressure can be used as EM reflectors, absorbers and scatters for its significant applications [3,4]. In this paper, a steady-state, one dimensional, nonuniform plasma slab used to coat cavities is studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, theoretical analysis and experimental researches show plasmas, which are generated by discharge in normal conditions, with certain parameters can attenuate microwaves significantly only in low frequency band. For microwaves in the high frequency band, attenuations become weak [6,7]. Conversely, the microwave absorptive material (MAM) with certain thickness can absorb microwaves in the high frequency band significantly, and absorb microwaves in the low frequency band weakly [8,9].…”
Section: Introductionmentioning
confidence: 99%